Unraveling the potential of CD8, CD68, and VISTA as diagnostic and prognostic markers in patients with pancreatic ductal adenocarcinoma - Fereshteh Rezagholizadeh; Fereshteh Rezagholizadeh; Fereshteh Rezagholizadeh; Fatemeh Tajik; Morteza Talebi; Morteza Talebi; Morteza Talebi; Seyed Reza Taha; Mahdieh Shariat Zadeh; Pooya Farhangnia; Pooya Farhangnia; Pooya Farhangnia; et al. (Frontiers in Immunology, 2024)
IntroductionPancreatic cancer is a truculent disease with limited treatment options and a grim prognosis. Immunotherapy has shown promise in treating various types of cancer, but its effectiveness in pancreatic cancer has been lacking. As a result, it is crucial to identify markers associated with immunological pathways in order to improve the treatment outcomes for this deadly cancer. The purpose of this study was to investigate the diagnostic and prognostic significance of three markers, CD8, CD68, and VISTA, in pancreatic ductal adenocarcinoma (PDAC), the most common subtype of pancreatic cancer.MethodsWe analyzed gene expression data from Gene Expression Omnibus (GEO) database using bioinformatics tools. We also utilized the STRING online tool and Funrich software to study the protein-protein interactions and transcription factors associated with CD8, CD68, and VISTA. In addition, tissue microarray (TMA) and immunohistochemistry (IHC) staining were performed on 228 samples of PDAC tissue and 10 samples of normal pancreatic tissue to assess the expression levels of the markers. We then correlated these expression levels with the clinicopathological characteristics of the patients and evaluated their survival rates.ResultsThe analysis of the GEO data revealed slightly elevated levels of VISTA in PDAC samples compared to normal tissues. However, there was a significant increase in CD68 expression and a notable reduction in CD8A expression in pancreatic cancer. Further investigation identified potential protein-protein interactions and transcription factors associated with these markers. The IHC staining of PDAC tissue samples showed an increased expression of VISTA, CD68, and CD8A in pancreatic cancer tissues. Moreover, we found correlations between the expression levels of these markers and certain clinicopathological features of the patients. Additionally, the survival analysis revealed that high expression of CD8 was associated with better disease-specific survival and progression-free survival in PDAC patients.ConclusionThese findings highlight the potential of CD8, CD68, and VISTA as diagnostic and prognostic indicators in PDAC.